Faktor-Faktor Yang Mempengaruhi Penggunaan Informasi Akuntansi Pada UMKM Kecamatan Kalidoni: Faktor-Faktor yang Mempengaruhi Penggunaan Informasi Akuntansi pada UMKM Kecamatan Kalidoni - Budi Kurniawan purba; M. Titan Terzaghi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The purpose of this study was to examine the effect of education, company age, and accounting training on the use of accounting information. The research method used is quantitative method using descriptive statistical analysis data analysis techniques, classical assumption test, validity test, reliability test, multiple regression analysis test, t test, f test, and coefficient of determination test using SPSS application. The population in this study were MSME actors registered in MSMEs in Kalidoni sub-district and several MSME actors found on Jalan Taqwa Mata Merah, Kalidoni District. Determination of the sample in this study using the Slovin formula and obtained a sample of 50 MSME entrepreneurs in Kalidoni sub-district. Secondary data is the data used in this study, the method for data collection is done by distributing questionnaires to MSME actors. Test the hypothesis by t test. with linear regression analysis of panel data with a significance level of 5%, the results of this study indicate that the variables of education, business age, and accounting training have a positive influence on the use of accounting information